2016
DOI: 10.4054/demres.2016.35.30
|View full text |Cite
|
Sign up to set email alerts
|

The Great Recession and America’s geography of unemployment

Abstract: BACKGROUNDThe Great Recession of [2007][2008][2009] was the most severe and lengthy economic crisis in the US since the Great Depression of the 1930s. The impacts on the population were multi-dimensional, but operated largely through local labor markets. OBJECTIVETo examine differences in recession-related changes in county unemployment rates and assess how population and place characteristics shaped these patterns. METHODSWe calculate and decompose Theil Indexes to describe recession-related changes in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 52 publications
1
52
0
1
Order By: Relevance
“…Over the study period, notable changes were observed in rates by urbanization level. A combination of factors, including economic and health indicators, likely contributed to the differences in annual suicide rate changes by urbanization level ( 14 18 ) observed in this study. Trends in suicide rates by sex, race/ethnicity, age group, and mechanism of death that are observed in the general population indicate that rates are consistently higher in rural communities.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Over the study period, notable changes were observed in rates by urbanization level. A combination of factors, including economic and health indicators, likely contributed to the differences in annual suicide rate changes by urbanization level ( 14 18 ) observed in this study. Trends in suicide rates by sex, race/ethnicity, age group, and mechanism of death that are observed in the general population indicate that rates are consistently higher in rural communities.…”
Section: Resultsmentioning
confidence: 85%
“…A closer look at annual rate changes revealed substantial increases after 2005 for large metropolitan counties, after 2008 for medium/small metropolitan counties, and after 2007 for nonmetropolitan/rural counties. Although the Great Recession officially began in 2007 and ended in 2009 ( 14 ), differential effects were observed at different points in different geographic areas ( 14 ). Economic indicators (e.g., housing foreclosures, poverty, and unemployment) vary by urbanization level, with rural areas usually having greater prevalence of these negative factors ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trends at the national level undoubtedly mask variation in poverty dynamics at lower levels, which has been shown to be the case in other dimensions of the recession's impact (Slack and Myers ; Thiede and Monnat ). With respect to poverty specifically, recent research by Iceland and Hernandez () and Jargowsky () supports the expectation of spatially uneven changes since 2000.…”
Section: Poverty and Spatial Inequality In The Rural United Statesmentioning
confidence: 99%
“…Overall, our findings contribute to well‐established literatures in rural sociology on spatial inequality and rural poverty, including work on “poor places” and concentrated poverty (Cotter ; Duncan ; Foulkes and Schafft ; Lichter and Johnson ; Lobao ; Lobao, Hooks, and Tickamyer ; Lobao and Saenz ; Nord, Luloff, and Jensen ; Tickamyer and Duncan ). We also add to the more recent literature on the spatially uneven impacts of the Great Recession (Rickman and Guettabi ; Slack and Myers ; Thiede and Monnat ; Ulrich‐Schad ; Ulrich‐Schad, Henly, and Safford ) and, we hope, provide an empirical basis for guiding social policy in rural America.…”
Section: Introductionmentioning
confidence: 95%
“…Recent evaluations of the Great Recession provide clear evidence that job loss and unemployment was not equally shared, but rather concentrated in areas with high concentrations of racial and ethnic minorities and individuals with low educational attainment (Thiede & Monnat, 2016). Areas with elevated unemployment experience greater unintentional injury of children (McClure, Kegler, Davey, & Clay, 2015), elevated preterm births (Messer et al, 2008), greater initiation of marijuana by adolescents (Tucker, Pollard, de la Haye, Kennedy, & Green, 2013), and more child maltreatment (Raissian, 2015).…”
Section: Empirical Reviewmentioning
confidence: 99%